PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOW BALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 019 SEKELADI - Wahidah Wahidah; Edddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem in this research was carried out because of the low of IPS study result of fourth grader of SD Negeri 019 Sekeladi, with the average class 67,78. Minimum Criteria of Completeness (KKM) IPS is 70. Among students who numbered 20 people only 7 people are complete. The formulation of the problem